Investigação da ionização do solo submetido a campo elétrico uniforme : análise de dados experimentais e modelagens - Allan Douglas Ferreira Corrêa (2020)
This master's thesis presents the results of the analyses related to the LRC soil database with regard to the tests carried out in a flat vat, under uniform field condition, in order to investigate the critical electrical field of soil ionization when subjected to lightning-characteristic currents. The literature on the topic presents some values of electric field for which the beginning of the process of soil ionization would take place. Some authors such as (OETTLÉ, 1988) and (MOUSA, 1994) establish the values of 1 MV/m and 0.3 MV/m respectively. On the other hand, (CIGRE, 1991) adopts 0.4 MV/m as a reference value. In view of this disparity in values, this research aims to contribute with more information on this topic. The analyzed database comprises high voltage tests on samples of 15 soils of different resistivities and humidities, for uniform and non-uniform electric field condition. For the study of the critical electric field, it is usual to use parallel plate vats which allow the application of a uniform field in soil samples. When this sample is subjected to impulsive waves, a high electric field can be established, causing a possible disruption in that medium. The analyzes showed that, in the resistivity range considered in the database (100 to 10,000 Ω.m), the critical electric field of soil ionization varies around 250 to 300 kV/m for soils up to 500 Ω.m, and from 300 to 400 kV/m for the rest of the considered resistivity range. Methodologies were also developed to evaluate the ionization of the samples, one through the accumulated energy of the applied impulses and the other based on electric field curves.